Model Matematika Penyakit Busuk Buah Kakao dengan Pengaruh Pengendalian Fungisida Nabati Lengkuas - Pangaribuan, Yohanes Mangasitua; winanda, rara sandhy (Journal of Mathematics UNP, 2024)
The cocoa fruit rot disease can be caused by the fungus Phytophthora palmivora. One way to prevent this disease is by using the galangal-based botanical fungicide. This research aims to understand the dynamics of cocoa fruit rot disease spread in a cocoa plant population with the influence of galangal-based botanical fungicide application. In the obtained model, equilibrium points are determined, and local stability analysis is conducted around these equilibrium points. The study also identifies critical points, represented by parameters that play a crucial role in stability changes within the given system. Analytical results are supported by numerical simulations, using parameter values obtained from relevant journals. Based on the analysis, there are two equilibrium points: the disease-free equilibrium point and the endemic equilibrium point. The disease spread analysis is influenced by the parameter value . If , the cocoa population remains free from disease spread, and conversely, if , the disease will spread in the population.